The relationship between Perceptual learning stype preperences in English and gender of frade 11 student at a hight school in Ben Tre province : - Lê, Thị Bích Phượng (Trường Đại học Cần Thơ, 2010)
The ways in which an individual characteristically acquires,retains,and retrieves information are collective termaed the individual's learning style(reid,1995).despite being included in 'individual differences' which can affect people langguage leraning,learning style has not been yetconsidered equally significant as other compoment in the leraning process,which might lead to the possibility that language teacher does not pay attention to their students'